Pelatihan Dan Implementasi Sistem Pertanian Terpadu Guna Maksimalisasi Hasil Tani Kelompok Lembur Ayu Farm - Syafrida Hafni Sahir; Siti Sabrina Salqaura; Siti Alhamra Salqaura (Forum Kerjasama Pendidikan Tinggi, 2024)
Sei Mencirim Village has a commodity focus on the agricultural and livestock sectors. The quality and quantity of agricultural and livestock products require an integrated ecosystem to support these sectors. This community service aims to increase knowledge and understanding related to the integrated agricultural system in creating an integrated ecosystem in the form of effectiveness and efficiency in the agricultural sector, as well as using agricultural waste as raw materials for livestock such as animal feed. Likewise, livestock waste can be utilized as raw material for compost fertilizer. The problems faced by Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency are the limited resources available, making the focus of economic sources only come from agriculture and animal husbandry. Meanwhile, the agricultural system techniques applied are still simple, community knowledge is still very limited in implementing an integrated farming system, and the a lack of knowledge related to social media-based marketing technology The target of this program is the Lembur Ayu Farm Group in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra. The methods used in this service are discussion and socialization, training, application of technology, mentoring, and evaluation. The community’s enthusiasm can be seen from the interactive activities of group members and the community while delivering materials, training, and question-and-answer discussions. . The interim results achieved are that the socialization and training activities of the integrated farming system are useful for agricultural interests, stated by 68.75% of the community as very useful, and 68.75% of the community stated that the implementation of this integrated farming system would be useful for increasing agricultural yields. Meanwhile, 31.25% of the community stated that it was useful. This program is expected to increase the insight of group members and the community regarding the practice of integrated agricultural systems in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency